Comparison of amyloid fibril formation by two closely related immunoglobulin light chain variable domains - Martin, Douglas J. (2010)
Light chain amyloidosis (AL amyloidosis) is a hematological disorder in which a clonal population of B cells expands and secretes enormous amounts of the immunoglobulin light chain protein. These light chains misfold and aggregate into amyloid fibrils, leading to organ dysfunction and death. We have studied the in vitro fibril formation kinetics of two patient-derived immunoglobulin light chain variable domain proteins, designated AL-09 and AL-103, in response to changes in solution conditions. Both proteins are members of the κI O18:O8 germline and therefore are highly similar in sequence, but they presented with different clinical phenotypes. We find that AL-09 forms fibrils more readily and more rapidly than AL-103 in vitro, mirroring the clinical phenotypes of the patients and suggesting a possible connection between the fibril kinetics of the disease protein and the disease progression.